Transcriptome analysis showed that tomato-rootstock enhanced salt tolerance of grafted seedlings was accompanied by multiple metabolic processes and gene differences - Wu, Xiaolei; Yuan, Ding; Bian, Xinyu; Huo, Ruixiao; Lü, Guiyun; Gong, Binbin; Li, Jingrui; Liu, Sichao; Gao, Hongbo (Frontiers in Plant Science, 2023)
Grafting is a commonly used cultural practice to counteract salt stress and is especially important for vegetable production. However, it is not clear which metabolic processes and genes are involved in the response of tomato rootstocks to salt stress. To elucidate the regulatory mechanism through which grafting enhances salt tolerance, we first evaluated the salt damage index, electrolyte permeability and Na+ accumulation in tomato (Solanum lycopersicum L.) leaves of grafted seedlings (GSs) and nongrafted seedlings (NGSs) subjected to 175 mmol·L− 1 NaCl for 0-96 h，covering the front, middle and rear ranges. Compared with the NGS, the GSs were more salt tolerant, and the Na+ content in the leaves decreased significantly. Through transcriptome sequencing data analysis of 36 samples, we found that GSs exhibited more stable gene expression patterns, with a lower number of DEGs. WRKY and PosF21 transcription factors were significantly upregulated in the GSs compared to the NGSs. Moreover, the GSs presented more amino acids, a higher photosynthetic index and a higher content of growth-promoting hormones. The main differences between GSs and NGSs were in the expression levels of genes involved in the BR signalling pathway, with significant upregulation of XTHs. The above results show that the metabolic pathways of "photosynthetic antenna protein", "amino acid biosynthesis" and "plant hormone signal transduction" participate in the salt tolerance response of grafted seedlings at different stages of salt stress, maintaining the stability of the photosynthetic system and increasing the contents of amino acids and growth-promoting hormones (especially BRs). In this process, the transcription factors WRKYs, PosF21 and XTHs might play an important role at the molecular level. In conclusion, the results of this study demonstrates that grafting on salt tolerant rootstocks can bring different metabolic processes and transcription levels changes to scion leaves, thereby the scion leaves show stronger salt tolerance. This information provides new insight into the mechanism underlying tolerance to salt stress regulation and provides useful molecular biological basis for improving plant salt resistance.